Designing Secondary Packaging for Skincare Products Using the Kansei Engineering Method - Faizi, Isnaini; Aprilia, Ika Riswi; Wati, Rahma; Sari, Novi Purnama (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2025)
The use of secondary packaging in skincare product bundles is essential for the shipping process. Relying solely on bubble wrap presents drawbacks, as it is non-reusable and lacks aesthetic value. The absence of optimal secondary packaging increases the risk of product damage during distribution and reduces visual appeal, ultimately affecting consumer perceptions of quality and brand credibility. Therefore, the design and development of suitable secondary packaging is necessary. This study aims to identify appropriate design elements based on user perceptions using the Kansei Engineering method, which has proven effective in product development. A total of 43 Kansei words were extracted from 39 packaging samples, resulting in two primary design concepts: “Practical-Modern” and “User Friendly- Untenable” The selected design elements include: leather and plastic materials (X1.6), pouch shape (X2.7), leather handle with divider (X3.7), four-sided flip-top closure (X4.9), modern design style (X5.1), and transparent red color (X6.10). The highest correlation value (PCC = 0.8963) was found in the “shape” element, indicating its strong influence on consumer perception. The final design was implemented as a physical mockup. Evaluation results showed that 59.4% of respondents preferred the design concept reflecting ease of use. Fuzzy Logic analysis confirmed these findings, placing the design in a neutral category leaning toward user-friendliness. These findings offer valuable insights into how emotional consumer preferences can inform secondary packaging strategies for skincare products.